تأثير السلوكيات الصحية على وظائف الكبد عند مرضى التهاب الكبد C - حلاج فاطمة; زيزفون حسان; يوسف دارين (Latakia University Journal -Medical Sciences Series, 2017)
يتأثر التهاب الكبد C إلى حد كبير بالسلوكيات البشرية ، ولا سيما تعاطي المخدرات والتدخين والنظام الغذائي و النشاط وتناول الكحول و السلوك الجنسي ، لذلك فإن تغيير السلوكيات المتبعة من قبل المريض يحد من تطور المرض ويمنع حدوث المضاعفات . الهدف: تقييم تأثير السلوكيات الصحية على وظائف الكبد عند مرضى التهاب الكبد C,المكان : أجريت هذه الدراسة في مركز التهابات الكبد الفيروسية المزمنة الملحق بالمشفى الوطني في محافظة اللاذقية. العينة : شملت الدراسة40 مريضاً . من المرضى المراجعين للمركز المذكور أثناء فترة إجراء الدراسة بين 30/10/ 2015و حتى 1/6 /2016. الأدوات : تمت مقابلة المرضى بشكل مستقل لجمع البيانات المطلوبة باستخدام استمارة البيانات الديموغرافية و الحيوية و معلومات المريض عن المرض وطبق دليل سريري على مرضى المجموعة الضابطة على ثلاث جلسات بالأسبوع يشمل الدليل السريري على الحمية و النظام العلاجي و النشاط والعادات ، ثم تم تقييم وظائف الكبد باستخدام معايير تشايد باغ بعد شهر وبعد ثلاثة أشهر وبعد ستة أشهر من الجلسة الثالثة. وتم تقييم التزامهم بالدليل السريري مرة واحدة أسبوعياً على مدى ستة أشهر .النتائج:تحسنت وظائف الكبد عند أفراد المجموعة التجريبية مقارنة بالمجموعة الضابطة , ويعود هذا التحسن إلى التزام المجموعة التجريبية بتطبيق الدليل السريري . التوصيات : تزويد مراكز التهاب الكبد الفيروسية بكتيبات توضيحية مزودة برسوم توضح كيفية تطبيق الدليل السريري( الحمية والنظام العلاجي و النشاط والعادات ) وأهمية الالتزام بها . Hepatitis C is affected by human behaviors especially drugs , diets ,activities smoking , sexy behaviors and alcohol , so it is very important to change health behaviors by patient to control of disease and avoid complications . Objective : to assess the effects of health behaviors on liver function among hepatitis C patients .Setting :The study was carried out in the Chronic Liver Hepatitis Center in Alwatany hospitalization in Lattakia province.Subjects::Thesample comprised 40 patients chosen randomly from the two genders who have hepatitis C out in the chronic liver hepatitis center in Alwatany hospitalization in Lattakia province during the research time. Tool :Data were collected using the following tools:Tool I Questionnaire: It was developed by the researcher and include items related to: demographic patients data , clinical data , questions about ( patients , information of disease , risk factors, healthy behaviors : (diet – treatment regimens – activities and habits)) Tool II : Liver function assessment sheet by using Child Pugh scale.Tool III :Patientcompliance check list which include questions about complianceGuidenceProshor.guide line has been developed by the researcherThe patients participated in 3 sessions .Each session (45minutes).Results: liver function were advanced of patient at the experimental group which applied the guide line more than patient at the control group because of Appling guide line .Recommendations : Chronic Liver Hepatitis Centers have been containing proshorsshow the impact of these health behaviors on the liver work and performing their functions as normal.